Nasal trumpet as a long-term remedy for obstructive sleep apnea syndrome in a child. (October 2021) - Yau, Tammy; Bansal, Ruchi; Hardin, Kimberly; Senders, Craig; Nandalike, Kiran
We present a case of successful long-term use of nasal trumpet for severe obstructive sleep apnea syndrome in a child with cerebral palsy and complex medical issues. Obstructive sleep apnea syndrome is frequently seen in pediatric patients with cerebral palsy due to their abnormal airway tone and pulmonary vulnerability. Identifying children with cerebral palsy who are at risk for obstructive sleep apnea syndrome is important because its treatment can improve quality of life and seizure control. Although first-line treatment for obstructive sleep apnea syndrome is adenotonsillectomy, children with cerebral palsy are more likely to have residual obstructive sleep apnea syndrome postoperatively. Other options such as positive airway pressure therapy and other upper airway surgeries may pose significant challenges and tolerance issues, as in our patient. As demonstrated in our report, the low rate of complications and ease of use make nasal trumpets a potential long-term treatment option for children with obstructive sleep apnea syndrome who fail or cannot comply with the traditional treatment options.